SMART CHICKEN FARM MONITORING AND INTERNET OF THINGS-BASED AUTOMATION SYSTEM - kukuh winarso; Rachmat Hidayat (International Journal of Science, Engineering, and Information Technology, 2022)
The use of intelligent technology in the modern era is widely used in all types of work. Technological developments in the livestock sector are so rapid, for example, with smart farming. Boiler chickens require temperatures of 29 – 35oC and humidity of 60 – 70% to maintain the life span and quality of the chickens. This study aims to build a Smart Chicken Farm monitoring system with automatic control based on the Internet of Things (IoT) with the fuzzy mamdani method as a decision-making system and mobile-based applications as monitoring media. After carrying out the testing process 5 times, the value generated from the sensor with fuzzy mamdani logic as decision making gives very good results characterized by no errors during the decision making process by fuzzy logic in setting ON and OFF on fans and heating lamps to maintain quality of temperature and humidity in smart chicken farm. The process of controlling and monitoring the smart chicken farm is applied in the form of a mobile-based application and runs well.